Disaster Mitigation Training to “Dokter Kecil” (Little Doctor) in Santa Maria and Santo Yusuf Cimahi Primary School - Pontjosudargo, Fransiska Ambarukmi (International Journal of Psychosocial Rehabilitation, 2020)
The “Dokter Kecil” (little doctor) partnership program is implemented with the purpose to forming healthy behaviours and disaster preparedness in Santa Maria and Santo Yusuf Primary School students, which located in Cimahi. Cimahi is located in the red zone of LembangFault disaster, so it has potential to geta very severe damage in the event of an earthquake due to displacement of Lembang Fault. In this program, the students were given the opportunity to do the simulation of disaster mitigation, doing the role of a doctor and a patient which were assisted by medical doctors and students of Faculty of Medicine, University of JenderalAchmadYani. This activity was a part of a community service, with the aim of increasing the knowledge and skills of community, especially primary school students in disaster mitigation to develop disaster preparedness of the students. The education and training were conducted on 33 participants “DokterCilik” in Santa Maria and Santo Yusuf Cimahi Primary school. The students conducted training, educational video screening, disaster mitigation simulation and control both before (pre-test) and also after the activity (post test).There was an increasing of knowledge, skills and attitude students after an intervention in the form of training, educational video screening and control both pre-test and post-test. Children had the ability to learn, use, provide, disseminate information and cooperate before and after emergencies.Various programs implemented with the full support of students is ultimately able to increase the understanding and attitutedof disaster mitigation and improve the ability of the school community in maintaining a healthy environment and disaster preparedness.